Soft sensor applications of RK-based nonlinear observers and experimental comparisons. Issue 1 (2nd January 2017) - Cetin, Meric; Beyhan, Selami; Iplikci, Serdar
Abstract: Soft sensing technology has still important industrial applications especially for chemical reactors, robotic applications, etc. Therefore, this paper introduces and applies novel Runge-Kutta (RK) discretization-based nonlinear observers for real-time sensing applications of unmeasurable quantities. The contribution of the paper is twofold. First, for reliability and accuracy, the stability of the RK based observers are proven. Second, they have been compared with well-known extended-Luenberger observer, extended-Kalman filter and sliding-mode observer on an experimental system. Experiments have shown that the RK model-based observers have a considerable place among conventional ones with respect to design issues and estimation performance for future soft sensing applications.